1879 N.C. Sess. Laws 355-56 - (:unkn) unknown (My University, 1879)
Ch. 198, §§ 1-7: Any tramp who shall enter any dwelling house or kindle any fire on the highway or on the land of another without the consent of the owner or occupant thereof, or shall be found carrying any firearms or other dangerous weapon, or shall threaten to do any injury to any person or to the real or personal estate of another, shall be punished by imprisonment at the discretion of the court, not to exceed twelve months.
Keywords: CARRY - DANGEROUS PERSONS